Analysing social, economic, technology and policy impacts on firm performance in Malaysia during the COVID-19 pandemic / Hui-Nee AuYong … [et al.] - AuYong, Hui-Nee; Ang, Shi-Wen; Yi-Huang Tan, Nathalie; Lee, Pei-Yan; Yow, Ying-Yan (2023)
This paper has the objective of assessing impacts during the COVID-19 pandemic on firms’ performance. The explanatory variables are social factor, technological factor, economic factor, and government policy intervention. The resource-based view (RBV) theory and stakeholder theory are the fundamental theories. The study focuses on primary data and applied stratified sampling method. There are 507 responses were collected from enterprises in Malaysia. Data analysis was generated with IBM SPSS Statistics version 28. In this paper, the reliability test result for all variables is excellent with no multicollinearity problem. Based on the results from multiple regression analysis, social factor, technological factor, economic factor, and government policy had a significant impact on Malaysian firms’ performance during the COVID-19 Pandemic. The two popular theories, Resource Based View (RBV) theory and Stakeholder theory were applied. To increase the firms’ performance, the company can continue to provide the working from home mode, adapt to the online platform and train their employees with fintech. Malaysia's economy growth is recovering; however, the inflation rate of the country is increasing. Thus, firms are recommended to minimize foreign exchange risk. As for the government, it should also simplify the funding program, maintain clear and transparent communication, provide subsidies firms that conduct e-commerce. Firm performance was affected by the social, economic, technological factors and the government policy. The initiatives led by the government assisted by the technological change brought by the fourth industrial revolution has moderated the social economic impact faced by the firms. Resource Based View (RBV) Theory and Stakeholder Theory were proven superior in illustrating the impacts on firm performance during the Pandemic.